Translating cultural differences: the meeting of Arabic and Malay cultures - Haji Ibrahim, Majdi; Abd. Rahman, Akmal Khuzairy (Persatuan Penterjemah Malaysia, 2009)
This paper aims at studying the differences between Arabic and Malay cultures from the perspective of translation studies. Thus, it is intended to uncover the problems of translating the culture-specific items between the two said languages. It also aims to shed some light on the related theories from the realm of translation studies with regard to translating cultural differences across languages. This will be done through presenting some samples of cultural categories from both languages and semantically analyzing the words that represent them. Finally, based on the observation of the problems that might arise from translating the differences, the paper will propose some related methods of translating in order to overcome the differences while at the same time preserving the communicativeness of the text.